The Impact of Pencak Silat Training at Night on Physical Fitness Levels - Hambali, Sumbara; Muharam, Ahmad; Hidayat, Yudi (CV Media Inti Teknologi, 2024)
Several pencak silat schools in Bandung in particular often carry out training at night. The pencak silat school at BTC performs this exercise from 10:00 PM to 3:00 AM. It is very interesting to research, especially its impact on physical fitness and overall healthThe purpose of this study is to assess how engaging in pencak silat training during the evening affects physical fitness. This investigation employs an ex post facto approach with a Contilation research design. The participants in this research were individuals who are part of the Pencak Silat Pencak Silat Faithful Heart Terate Brotherhood in Bandung City. The research instrument uses the Multistage Fitness Test. Using quantitative survey data analysis techniques. Based on data analysis, it was concluded that there was an influence for training pencak silat focuses on physical fitness and takes place in the evening.. The results of the study showed that members of the Bandung City Pencak Silat Brotherhood Setia Hati Terate had a diverse distribution of fitness levels: 13.6% had a low fitness level, 40.9% had a medium fitness level, 36.4% had a fair fitness level, 9.1 % achieved a good level of fitness, while none achieved a high level of fitness. Consequently, it can be inferred that practicing pencak silat at nighttime yields favorable results, even though it is not significant or only reaches a moderate fitness level. This is mainly due to the intensity of training which tends to be low and does not increase consistently over time, resulting in slow and non-optimal physical improvement.